FLOWERING SYNDROME – HYBRID PERFORMANCE RELATIONSHIP IN MAIZE 2- Yield and yield components - & et al., Al- Khazaali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Field experiment during four seasons (spring and fall 2014 and 2015) was carried out on maize at the experimental field of Field Crop Dept., Agric. Coll., Univ. of Baghdad to study the role of selection for early and late flowering (silking) of inbred lines on the grain yield of the consequent hybrids. Four inbred lines (Zm19, Zm32, Zm51 and Zm61) and two testers (Zm21 late and Zm60 early silking) were used. In the first two seasons, the seeds of the four inbred lines were planted, first 10 plants that flowered early and 10 plants that flowered late were selected, the seeds of the selected plants were multiplied. The seeds of the early and late selected inbred lines were planted in the third season and then crossed with testers. Crosses from the early and late silking (ELS) were produced and their seeds were cultivated in the last season. Comparison in some growth traits, yield and its components were conducted among the crosses. The experiments were laid out in randomized complete block (RCBD) with three replicates. The selection for parents of early and late silking has significantly influenced the Grain Yield (GY), the cross Zm19xZm60 (produced from crossing parents of early silking selected from inbred lines - PESSIL) has surpassed in the GY on its counterpart (produced from parents of late silking selected from inbred lines) (10.516 and 8.188 ton.ha-1 sequentially). The testers (Zm21 late silking and Zm60 early silking - ES) have significantly differed in their effect on the traits of some hybrids (produced from crossing) especially the GY when crossed with ES parents. The cross (Zm19 x Zm60) which produced from crossing the tester Zm60 with the ES parents selected from the inbred line Zm19 has surpassed the cross Zm19 x Zm21, which produced from crossing the tester Zm21, with PESSIL Zm19 in GY (10.516 and 6.642 mt ha-1 ton.ha-1, sequentially). Selection has also shown significant differences in several traits, the most prominent are the Seed’s Growth Rate (SGR). It can be conclude that selection for ES and LS inbred lines and testers’ effect have a great importance in deriving hybrids of a high yield and several traits.